Differentiation of Clonal Complex 59 Community-Associated Methicillin-Resistant Staphylococcus aureus in Western Australia - Coombs, Geoffrey W. (American Society for Microbiology (ASM), 2010)
Clonal complex 59 (CC59) community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) strains were characterized using pulsed-field gel electrophoresis, spa typing, multilocus sequence typing, diagnostic DNA microarrays, and PCRs targeting staphylococcal cassette chromosome mec (SCCmec) elements and Panton-Valentine leukocidin (PVL). Six distinct groups within CC59 were characterized. At least seven different variants of SCCmec elements were identified (IVa [2B], IVb [2B], IVd [2B], IV variant [2B], IVa [2B&5], V variant [5C2], and V [5C2&5]). (The structural type is indicated by a Roman numeral, with a lowercase letter indicating the subtype, and the ccr complex and the mec complex are indicated by an Arabic numeral and an uppercase letter, respectively. Where there is an extra ccr element, this is indicated by “&” and an Arabic numeral designating the ccr type.) The first group is similar to the American sequence type 59 (ST59) MRSA-IV CA-MRSA strain USA1000. The second group includes a PVL-negative ST87 strain with an SCCmec element of subtype IVb (2B). The third group comprises PVL-variable ST59 MRSA-IV strains harboring multiple SCCmec IV subtypes. PVL-negative ST59 MRSA strains with multiple or composite SCCmec elements (IVa [2B&5]) form the fourth group. Group 5 corresponds to the internationally known “Taiwan clone,” a PVL-positive strain with a variant SCCmec element (V [5C2&5]). This strain proved to be the most common CC59 MRSA strain isolated in Western Australia. Finally, group 6 encompasses the ST59 MRSA-V variant (5C2). The differentiation of CC59 into groups and strains indicates a rapid evolution and spread of SCCmec elements. Observed differences between groups of strains as well as intrastrain variability within a group facilitate the tracing of their spread.